Spontaneous Recanalization after Vasectomy - Antônio Marmo Lucon; Fábio Firmbach Pasqualotto; Edison Daniel Schneider-Monteiro; Luis Balthazar Saldanha; Alexandre Danilovic (The Scientific World Journal, 2006)
Vasectomy is the method most commonly used in men for voluntary sterilization purposes. We report two cases of early recanalization following vasectomies performed in 1085 men for sterilization purposes at a tertiary public institution between January 2000 and November 2003. Thus, the risk of 0.2% of failure due to early recanalization should be explained and the fertility implications stressed. Written documentation recording the clarification presented at consultation is essential.